2016
DOI: 10.1016/j.jcrs.2015.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of refractive and visual outcomes with centration points 80% and 100% from pupil center toward the coaxially sighted corneal light reflex

Abstract: Both 80% centration and 100% centration were safe and effective. Compared with the 100% group, the 80% group had less astigmatism and less undercorrection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…The coaxially sighted corneal light re ex piont is the corneal entry point of the visual axis [5] .Studies have shown that coaxially sighted corneal light re ex piont is the ideal ablation centration point, because coaxially sighted corneal light re ex piont is the closest point to the visual axis and is not affected by changes of pupil size and center position, with an average of 0.02 mm [6] .Therefore, the angle kappa can be understood as P-Dist [7] .However, the angle kappa is not a xed value, and changes with the dynamic change of the pupil center position [8,9] .That is why it is necessary to further explore the dynamic changes of the pupil size and center position suitable for excimer laser surgery, P-Dist and its correlation with other biomechanics.The related research at home and abroad hasn't been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The coaxially sighted corneal light re ex piont is the corneal entry point of the visual axis [5] .Studies have shown that coaxially sighted corneal light re ex piont is the ideal ablation centration point, because coaxially sighted corneal light re ex piont is the closest point to the visual axis and is not affected by changes of pupil size and center position, with an average of 0.02 mm [6] .Therefore, the angle kappa can be understood as P-Dist [7] .However, the angle kappa is not a xed value, and changes with the dynamic change of the pupil center position [8,9] .That is why it is necessary to further explore the dynamic changes of the pupil size and center position suitable for excimer laser surgery, P-Dist and its correlation with other biomechanics.The related research at home and abroad hasn't been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Only Zhang et al used the femtosecond laser to create the corneal flap, while others used the microkeratome [17]. A study by Chang et al which compared the difference in locating the centration point between 80 and 100% from the pupil center toward the CSCLR did not meet the inclusion criteria and was thus excluded from this meta-analysis [20]. Another study reported by Okamoto et al in 2009 was also excluded because the subjects may have also been involved in the one published in 2011 for the same observation period and short follow-ups [15,21].…”
Section: Resultsmentioning
confidence: 99%
“…Especially with premium lenses such as toric, enhanced depth of focus (EDOF) or multifocal lenses [ 2 ] or with enhanced excimer or femtosecond laser refractive surgery procedures [ 3 15 ] large angles Alpha or Kappa were identified as potential risk factors for an unsatisfactory outcome. In corneal refractive surgery, centration of the corneal ablation pattern can be directly performed based on the corneal centre (limbus centre [ 16 ]), pupil centre [ 17 ], or the Purkinje reflex PI originated from a coaxial light source in the surgical microscope [ 5 , 12 ], and the benefits and drawbacks of the different centring strategies has been discussed controversially in many scientific papers. In contrast, in cataract surgery intraoperative centration of the lens implant could be performed with some restrictions [ 18 ], but the final lens position is mostly determined by wound healing effects and capsular shrinkage in the postoperative interval [ 8 ].…”
Section: Introductionmentioning
confidence: 99%